Researching Risk: Narrative, Biography, Subjectivity - Karen Henwood; Nick Pidgeon; Karen Parkhill; Peter Simmons (Forum: Qualitative Social Research, 2010)
This article contributes to the development of methodological practices promoting greater epistemic reflexivity in risk research and in social science generally. Knowledge of the specific practices researchers will find useful cannot exist separately from any particular empirical project. Accordingly, we report on, and provide a reflective account of, the "nuclear risk" project that was part of the Social Contexts and Responses to Risk (SCARR) network in the UK (2003-2008). A key focus is exploring the value of narrative methods—especially narrative elicitation methods—for understanding people's perceptions of, and ways of living with, risk. We credit our deployment of a narrative method with producing a rich form of data on risk-biography intersections, which have carried great significance in our analytical work on the way biographical experiences, dynamically unfolding through space and time, can be interrupted by risk events. Arguments from the literature on reflexive modernity are deployed to make the case for: researching risk in everyday life as a problematic in and of itself; placing concepts of risk-biography, risk-reflexivity and risk-subjectivity at centre stage; and finding ways to inquire into the social and psychic complexities involved in the dynamic construction and reconstruction of risk phenomena. URN: urn:nbn:de:0114-fqs1001201